2021
DOI: 10.1111/apa.15756
|View full text |Cite
|
Sign up to set email alerts
|

Complicated appendicitis due to diagnosis delay during lockdown period in Italy

Abstract: Although children seem to be less affected than adults by COVID-19, Italian paediatric hospitals have had to significantly reorganise services to deal with the pandemic. These include the tertiary-level Gaslini Children's Hospital in Genoa, which handles around 35,000 emergency room (ER) visits per year. The Government lockdown has dramatically reduced ER admissions and delayed programmed admissions. 1 We noticed this from the first verified cases of COVID-19 in Italy, and ER visit fell significantly after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
1
10
2
1
Order By: Relevance
“…On the other hand the concomitant fear of acquiring SARS-CoV-2 infection during ED stay, could induce to avoid access to hospital care, even in presence of severe clinical conditions, with the risk of diagnostic delay as reported by others [1][2][3][4][5]. However, according to the triage urgency code only, we did not observe an increase of patients assessed for critical conditions (red and yellow code).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…On the other hand the concomitant fear of acquiring SARS-CoV-2 infection during ED stay, could induce to avoid access to hospital care, even in presence of severe clinical conditions, with the risk of diagnostic delay as reported by others [1][2][3][4][5]. However, according to the triage urgency code only, we did not observe an increase of patients assessed for critical conditions (red and yellow code).…”
Section: Discussioncontrasting
confidence: 40%
“…Possible reasons for this decrease were the reduction of other seasonal infections due to self-isolation, the recommendation not to use the ED in the absence of serious conditions, and, above all, the fear of patients and parents of being infected with SARS-CoV-2. Most of the non-emergent diseases usually seen at our pediatric ED have been avoided but, one of the most negative consequences was delayed access to pediatric emergency facilities, even for the most severe non-SARS-CoV-2 related conditions [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This result is discordant with other Australian studies, with increased rates of complicated appendicitis reported at a major paediatric tertiary centre in Queensland during the pandemic, despite improved availability of emergency operating theatres. 6 Internationally, similar findings of increased rates of complicated appendicitis have been reported in paediatric patients in Italy, 7 and in both paediatric 8 and adult cohorts 9 in Germany where appendicitis was used in these studies as a proxy for the investigation of delayed presentation to hospital more generally. Our findings suggest there may not be a similar reluctance to seek healthcare in Victoria despite extended periods of lockdown and stay at home orders.…”
Section: Discussionsupporting
confidence: 68%
“…9 studies examined the effect of COVID-19 on the rate of complicated appendicitis in children, covering 2065 children (1650 before and 415 during the pandemic) [ [42] , [43] , [44] , [46] , [47] , [48] , [49] , 52 , 60 ]. There was a trend seen towards more CA during the pandemic, but this effect is without statistical significance (P = 0.12).…”
Section: Resultsmentioning
confidence: 99%